1992
DOI: 10.1088/0953-4075/25/7/005
|View full text |Cite
|
Sign up to set email alerts
|

A scaling law for oriented s-p excitation in ion-atom collisions

Abstract: Based on a first-order straight-line path SCA calculation a general expression for the angular momentum orientation parameter Lperpendicular to for direct s-p excitation is determined. The derived scaling relation is in excellent agreement with multi-state close-coupling computations for s-p excitations in H+-H (1s) and H+-Na (3s) collisions at intermediate to high projectile energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…[10][11][12] Cocaine is highly lipophilic, so much so that treatment of cocaine overdose includes the administration of lipid emulsions to dampen its effects. 13 Cocaine is also hydrophilic; the hydrochloride salt is readily soluble in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Cocaine is highly lipophilic, so much so that treatment of cocaine overdose includes the administration of lipid emulsions to dampen its effects. 13 Cocaine is also hydrophilic; the hydrochloride salt is readily soluble in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Administered both as the hydrochloride salt and in its freebase form, both forms of cocaine are very addictive and have similar pharmacological effects. 14,15 Although it has been stated that cocaine is active only in its protonated form and that cocaine crosses the BBB only as a freebase (or in its deprotonated form), 16 this is not necessarily the case, 17 especially given that crystallographic investigations of cocaine molecules bound into a protein receptor the cocaine molecule appear to be deprotonated 12 and measurement of cocaine as it crosses the BBB in vivo is not yet possible.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the orientation phenomena in electron-ion or electron-atom collisions [5][6][7][8] have been investigated since these phenomena provide an understanding of the characteristics of plasmas. Recent experimental investigations demonstrate the possibility of the detection of radiative transitions from excited p ±1 (m = ±1) states to the ground state [8].…”
Section: Introductionmentioning
confidence: 99%
“…7 Since then the orientation phenomena in the atomic transitions have been actively investigated because these phenomena provide detailed information on the mechanism of the collisional excitations of the target system. [8][9][10] The interaction potential in classical plasmas has been usually represented by the Yukawa-type Debye-H€ uckel model since the average energy of interaction between charged particles is smaller than the average kinetic energy of a particle. 11,12 Moreover, it is found that with an increase of the plasma density the multiparticle correlation caused by simultaneous interaction of many charged particles should be taken into account to describe the effective interaction potential in dense plasmas.…”
Section: Introductionmentioning
confidence: 99%